Stalins Soldaten in Österreich : die Innensicht der sowjetischen Besatzung 1945 - 1955 - Stelzl-Marx, Barbara 1971- (Kriegsfolgen-Forschung, 2012)
As Soviet troops first set foot on Austrian territory on March 29, 1945 near Klostermarienberg, they found themselves in a hostile, perplexing and largely unknown world. The Austrians by no means greeted their Eastern "liberators from the fascist yoke" with open arms. Given the first encounters with the Austrian population a variety of stereotypes developed, supporting images of the enemy and the other. Soviet propaganda together with the war experiences anchored these ideas deep into the sub-conscious. However, also ideas of the West that had been aroused by film and literature were now confronted with reality.The Red Army's glorious and triumphant end of WWII was followed by their ten-year long occupation of Austria, where hundreds of thousands of Soviet soldiers and officers, their wives and children and also civil occupational personnel were linked to Austria for many months and sometimes even years. Moscow attempted (often in vain) to train their troops in line with a "higher political oversight," to boost their military discipline and to strengthen their "political and moral status." From the Soviet point of view, direct confrontation with the Austrian population, but also the Western occupying forces rescued them from the danger of being a "hostile takeover." Doubts about the superiority of the Communist system, breaches of regulations as well as offences, which were really "only" a matter of criminal law, were considered politically motivated and served as a sign of the ideological and political fickleness of the concerned party. Reprisals for the afore-mentioned infractions could be severe and sometimes meant the death penalty.The Austrian view of occupation, Austrian everyday life in the Soviet occupation zone or the most important Topoi from the Red Army is well documented and preserved. This research is owed largely to the individual experiences, impressions and responses of the occupying forces themselves.This work is focused on the EXPERIENCE of the soviet "lifeworld" in Austria, which includes among other things the occupation organization, the discipline and prosecution, the daily work, the everyday live in the barracks or the leisure activities; the PERCEPTION mirrored in written and oral testimonies and the institutionalized as well as private MEMORY in the former Soviet Union. The beginning depicts the macro-level structure and functioning of the Soviet occupational apparatus as well as the historical background. This meticulous retracin ...